Adaptation and Codon-Usage Preference of Apple and Pear-Infecting Apple Stem Grooving Viruses - Jaedeok Kim; Aamir Lal; Eui-Joon Kil; Hae-Ryun Kwak; Hwan-Su Yoon; Hong-Soo Choi; Mikyeong Kim; Muhammad Ali; Sukchan Lee (Microorganisms, 2021)
Apple stem grooving virus (ASGV; genus Capillovirus) is an economically important virus. It has an approx. 6.5 kb, monopartite, linear, positive-sense, single-stranded RNA genome. The present study includes identification of 24 isolates—13 isolates from apple (Pyrus malus L.) and 11 isolates from pear (Pyrus communis L.)—from different agricultural fields in South Korea. The coat protein (CP) gene of the corresponding 23 isolates were amplified, sequenced, and analyzed. The CP sequences showed phylogenetic separation based on their host species, and not on the geography, indicating host adaptation. Further analysis showed that the ASGV isolated in this study followed host adaptation influenced and preferred by the host codon-usage.